Microbial resources from functional existence in nature to applications - Kurtboke, Ipek (Academic Press, an imprint of Elsevier, 2017)
Microbial Resources: From Functional Existence in Nature to Applications provides an exciting interdisciplinary journey through the rapidly developing field of microbial resources, including relationships to aspects of microbiology. Covers the functional existence of microorganisms in nature, as well as the transfer of this knowledge for industrial and other applications. Examines the economic perspective of revealing the potential value of microbial material and figuring it into socio-economic value; legal perspectives; and how to organize a fair allotment of socio-economic benefits to all stakeholders who have effectively contributed to the preservation, study, and exploitation of microbiological material.-Provided by publisher.